STYLISTIC EXPLORATION AND PERSPECTIVES OF THE TUWALI IFUGAO YOUTH IN WESTERN LAGAWE ON HUDHUD - Eustaquio, Ma. Theresa; Luagna, Lez Mar (International Journal of Arts, Sciences and Education, 2024)
Hudhud is one of the traditions of the Ifugao that is passed down from generation to generation. An ancient and culturally significant ritual among the Ifugao people is the chanting of the Hudhud, which is a rhythmic and melodic recital of the epic poems. Using a descriptive-qualitative design the researcher interviewed 48 students from the Western part of Lagawe who can perform the hudhud. Despite the archaic language that was used in hudhud, it still turns out that there are students of Western Lagawe who are still aware of the theme of the hudhud. Though the student feel so much nervousness especially to those who perfoms the hudhud for the first time. It can indeed provide one with a strong sensation of immersion and historical connection.